KINERJA ROTATED CODED 8 PSK PADA KANAL RAYLEIGH - Linda Meylani; Nur Andini; Iswahyudi Hidayat; Hurianti Vidyaningtyas (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2018)
Signal space diversity is a one of techniques to increase the performance of system without using error control coding technique, adding power transmission or reduce data rate but with rotate the signal constellation. With the aim to increase performance of MC CDMA, this paper combine rotated and trellis 8 PSK coded modulation scheme. From the simulation results, rotated modulation doesn’t give any coding gain to system in AWGN channel, the performance of rotate modulation scheme and system MC CDMA without rotate scheme was relative have same performance. Different things happened in fading channel. Rotated modulation scheme give a better performance rather than system without rotate scheme. Coded modulation in the other side give a coding gain to the system in AWGN channel or in Rayleigh fading channel.